JIWA KEWIRAUSAHAAN PELAKU AGROINDUSTRI KOPI DI KOTA BUKITTINGGI - Hariance, Rica; Putri, Afrianingsih; Nofialdi, Nofialdi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
The growing number of coffee agro-industries, the increase of consumers’ interest in coffee, and the challenges of industrial revolution 4.0, are driving demand for improving coffee agro-industry business. It encourages entrepreneurs to develop their entreprenuerial skills. This study aims to analyze the entrepreneurial spirit of the coffee agro-industry’s entrepreneur in Bukittinggi city in encountering industrial revolution 4.0. Bukittingi was selected as the study area due to leading tourist destinations in West Sumatera and its coffee agro-industry known as